(untitled) (REMUNOM, 2025)
Objectives: To describe the psychomotor activities performed with children aged 3 to 5 years in Primary Care at a Municipal Early Childhood Education Center (CMEI) in the municipality of Teresina-PI, highlighting the effects on the motor, cognitive, and spatial development of the schoolchildren. Methodology: This is an experience report describing the psychomotor activities developed with children aged 3 to 5 years at a CMEI located in Teresina-PI, within the context of Primary Health Care, involving physiotherapy students, physiotherapy professionals, physical education professionals, and the pedagogical team. Results: Children from different classes aged 3 to 5 years participated, with activities applied continuously, respecting the pace of the classes and the pedagogical planning. The activities allowed observation of motor and cognitive development, highlighting strengths and difficulties of each age group. Most children demonstrated age-appropriate performance, with agility in the proposed activities. A smaller number showed difficulties, especially in tasks involving gross motor skills and balance. The evaluated children performed well in fine motor skills, body schema, and spatial organization. Conclusion: Therefore, it was understood that assessments are essential to identify progress and difficulties, allowing attentive observation of those with below-expected performance, recommending multiprofessional follow-up and targeted interventions.